Phase II trial of the IDO pathway inhibitor indoximod plus pembrolizumab for the treatment of patients with advanced melanoma. Issue 6 (11th June 2021) - Zakharia, Yousef; McWilliams, Robert R; Rixe, Olivier; Drabick, Joseph; Shaheen, Montaser F; Grossmann, Kenneth F; Kolhe, Ravindra; Pacholczyk, Rafal; Sadek, Ramses; Tennant, Lucinda L; Smith, Christopher M; Kennedy, Eugene P; et al.
Abstract : Background: The indoleamine 2, 3-dioxygenase (IDO) pathway is a key counter-regulatory mechanism that, in cancer, is exploited by tumors to evade antitumor immunity. Indoximod is a small-molecule IDO pathway inhibitor that reverses the immunosuppressive effects of low tryptophan (Trp) and high kynurenine (Kyn) that result from IDO activity. In this study, indoximod was used in combination with a checkpoint inhibitor (CPI) pembrolizumab for the treatment for advanced melanoma. Methods: Patients with advanced melanoma were enrolled in a single-arm phase II clinical trial evaluating the addition of indoximod to standard of care CPI approved for melanoma. Investigators administered their choice of CPI including pembrolizumab (P), nivolumab (N), or ipilimumab (I). Indoximod was administered continuously (1200 mg orally two times per day), with concurrent CPI dosed per US Food and Drug Administration (FDA)-approved label. Results: Between July 2014 and July 2017, 131 patients were enrolled. (P) was used more frequently (n=114, 87%) per investigator's choice. The efficacy evaluable population consisted of 89 patients from the phase II cohort with non-ocular melanoma who received indoximod combined with (P). The objective response rate (ORR) for the evaluable population was 51% with confirmed complete response of 20% and disease control rate of 70%. Median progression-free survival was 12.4 months (95% CI 6.4 to 24.9). The ORR for Programmed Death-Ligand 1 (PD-L1)-positive patients was 70% compared with 46% for PD-L1-negative patients. The combination was well tolerated, and side effects were similar to what was expected from single agent (P). Conclusion: In this study, the combination of indoximod and (P) was well tolerated and showed antitumor efficacy that is worth further evaluation in selected patients with advanced melanoma.